Estimating Some Social and Environmental Effects from Rail/Road Substitution in the Trans-European Transport Corridors - Janic, Milan; Jovanović, Tomislav (Promet - Traffic&Transportation, 2012)
This paper deals with estimating possible effects in terms of mitigating the social and environmental impacts which could be achieved by operating the rail freight train instead of the road truck services in the given Trans-European transport corridor during the specified period of time. In general, these impacts embrace noise, congestion, traffic incidents/accidents (Safety), and energy consumption and related GHG emissions (Greenhouse Gases). Each type of impact, specific to particular mode, is analyzed and modeled, thus enabling its quantitative estimation and intermodal comparison under the given circumstances. In particular, energy consumption and related GHG emissions and their costs have been under focus. The total costs of the above-mentioned impacts in the given case have also been estimated. Thus, they both represent a solid base for the assessment of the social-environmental feasibility of the future similar cases.